The Search for Potential Remediation Strategies and Sustainable Alternatives for Safe use of US EPA Superfund Sites - Anyiam Ngozi Donald; Brian Leslie Sanders; Matthew Halma (Trends in Ecological and Indoor Environmental Engineering)
Background: Environmental contamination from US EPA Superfund sites has long posed a serious threat to public health and environmental sustainability. Increased environmental risk in areas near US EPA Superfund sites is evidenced by studies that have found that these areas are characterized by higher levels of toxic substances in the soil and air. Addressing the hazards these sites pose requires thoughtful planning and creative approaches that balance environmental restoration with community development goals. Reclaiming abandoned industrial and mining sites is imperative because it is an opportunity to enhance public safety, restore ecosystems and support communities.